Comparison between conventional design and cathode gas recirculation design of a direct-syngas solid oxide fuel cell–gas turbine hybrid systems part II: Effect of temperature difference at the fuel cell stack - Azami, Vahid; Yari, Mortaza (International Journal of Renewable Energy Development, 2018)
This study focuses on the effect of the temperature difference at the fuel cell stack (ΔTcell) on the performances of the two types of SOFC–GT hybrid system configurations, with and without cathode gas recirculation system. In order to investigation the effect of matching between the SOFC temperature (TSOFC) and the turbine inlet temperature (TIT) on the hybrid system performance, we considered additional fuel supply to the combustor as well as cathode gas recirculation system after the air preheater. Simulation results show that the system with cathode gas recirculation gives better efficiency and power capacity for all design conditions than the system without cathode gas recirculation under the same constraints. As the temperature difference at the cell becomes smaller, the both systems performance generally degrade. However the system with cathode gas recirculation is less influenced by the constraint of the cell temperature difference. The model and simulation of the proposed SOFC–GT hybrid systems have been performed with Cycle-Tempo software.Article History: Received January 16th 2018; Received in revised form July 4th 2018; Accepted October 5th 2018; Available onlineHow to Cite This Article: Azami, V and Yari, M. (2018) Comparison Between Conventional Design and Cathode Gas Recirculation Design of a Direct-Syngas Solid Oxide Fuel Cell–Gas Turbine Hybrid Systems Part II: Effect of Temperature Difference at The Fuel Cell Stack. International Journal of Renewable Energy Development, 7(3), 263-267.http://dx.doi.org/10.14710/ijred.7.3.263-267